Factors Associated with Ophthalmic Complication among Diabetic Patients aged 40 Years or More: Findings of a Hospital-based Study (Sir Salimullah Medical College Journal, 2022)
Background: Estimates in 2017 indicate that in South-East Asian region, 8.5% of the adult population (82 million people) aged 20-79 years are diabetic. Diabetic Retinopathy is most common among the ophthalmic complications being the fifth leading cause of global blindness. Our objective was to find out the socio-demographic and varied risk factors related to the development of ophthalmic complications in Bangladesh.Methodology: We conducted a cross sectional study among diabetic patients attending the out-patient department of Bangladesh Institute of Health Science General Hospital from July 2017 to June 2018. The study population included 289 diabetic patients aged e”40 years. The impact of age, physical exercise, duration of diabetes, fasting blood glucose level, treatment with insulin and co-morbidity with hypertension, dyslipidaemia and nephropathy on the likelihood of developing ophthalmic complications was assessed using binary and multivariable logistic regression.Results: The average age of the patients was 60.2±9.3 years and 181 (63.0%) patients were male. Most of the respondents (97.9%) were suffering from type 2 diabetes. Participants have been suffering from diabetes for on an average of 10.9±7.9 years. From multivariable logistic regression we found that those who had been suffering from diabetes for over 10 years, were almost 4 times more likely to have ophthalmic complications. Patients aged more than 60 years had 3 times greater odds for having ophthalmic complications when adjusted for other variables.Conclusion: Patients with older age and greater duration of diabetes are more susceptible to ophthalmic complication, thus public health interventions must be formulated accordingly.Sir Salimullah Med Coll J 2021; 29(2): 87-94